Governança ambiental na coleta seletiva de resíduos sólidos urbanos no município de Fortaleza-CE - Fernandes, Yana Beltrão (2023)
Excessive generation and environmentally inadequate final disposal of solid waste constitute two of the main environmental and public health challenges of modern society. In Brazil, to address these issues, in 2010, the National Solid Waste Policy (PNRS) was published, through Law No. 12.305/2010. The City of Fortaleza, Ceará, to meet PNRS requirements, implemented equipment aimed at selective collection that did not achieve the expected success. To shed light on the issue, this study used the concept of environmental governance to investigate the relationships between the social actors involved in selective collection in Fortaleza and identify the factors that may have affected its performance. From this perspective, the main objective of this study was to understand how environmental governance or lack thereof affects the efficiency of selective collection of urban solid waste in the context of the municipality of Fortaleza-CE. The research, qualitative in nature, is characterized as a case study whose analysis of environmental governance was carried out from the perspective of social actors. Data were collected through interviews with relevant social actors, divided into two groups: Official Interest Group (represented by the Public Power) and Collective Interest Group (represented by civil society); who evaluated the central elements of good governance, classified according to the World Bank, as: accountability, participation, decentralization and transparency. The results showed that the main factors that affected the environmental governance of selective collection were: (i) insufficient financial resources; (ii) market conditions for recyclable materials; (iii) the level of knowledge and environmental awareness of the population regarding selective collection; (iv) the degree of population participation; (v) charging for the waste collection service; and (vi) the absence of an information campaign for the population. The social actors pointed out actions that the City of Fortaleza needs to carry out to improve the environmental governance of selective collection in Fortaleza, such as designing mechanisms to increase social participation in selective collection programs, greater dissemination of the results obtained in the program and greater integration and coordination between City Hall bodies in order to strengthen environmental governance. Furthermore, it is important that City Hall promotes clear dissemination of information that allows citizens and society in general to compare and evaluate government actions in terms of fulfilling the commitments made to the population.